Brain volumes in relation to loneliness and social competence in preadolescents born very preterm - Annika Lind; Susanna Salomäki; Riitta Parkkola; Leena Haataja; Päivi Rautava; Niina Junttila; Juha Koikkalainen; Jyrki Lötjönen; Virva Saunavaara; Riikka Korja on behalf of the PIPARI Study Group (United Kingdom, 2022)
Introduction
The aim of the present study was to assess how regional brain volumes associate with self‐experienced social and emotional loneliness and social competence in very preterm and term‐born preadolescents.
Materials and methods
Thirty‐four very preterm subjects (birthweight ≤1,500 g and/or gestational age <32 weeks) without neurodevelopmental impairments and/or major brain pathologies and 31 term‐born subjects underwent magnetic resonance imaging at 12 years of age. Regional brain volumes were measured using an automated image quantification tool. At 11 years of age, social and emotional loneliness were assessed with the Peer Network and Dyadic Loneliness Scale‐self‐report questionnaire and cooperating skills, empathy, impulsivity, and disruptiveness with the Multisource Assessment of Children's Social Competence Scale‐self‐report questionnaire.
Results
In the very preterm group, a number of significant associations were found between smaller regional brain volumes and self‐experienced emotional loneliness, more impulsivity and more disruptiveness. In the control group, brain volumes and loneliness were not associated, and brain volumes and social competence were associated with a lesser degree than in the very preterm group.
Conclusion
Experiences of emotional loneliness and poorer social competence appear to be more related to brain volumes in very preterm preadolescents than in those born full‐term. It also appears that in very preterm preadolescents, emotional loneliness may be more reflected in brain development than social loneliness.